Development and Feasibility of Tablet-based 24-hour Recall for Dietary Intake and Recipe Collection Among Adults and Children in Tanzania (P10-018-19). (13th June 2019) - Ambikapathi, Ramya; Irema, Imani; Lyaatu, Isaac; Mosha, Dominic; Nyamsangia, Stella; Kajuna, Deus; Kumalija, Elfrida; Galvin, Lauren; Caswell, Bess; Kazonda, Patrick; Leyna, Germana; Killewo, Japhet; et al.
Abstract: Objectives: In many regions of the world, little is known about food consumption, meal structures, meal patterns, and nutrient intake. Collection of these data using quantitative dietary intake is expensive and labor intensive. Thus, many programmatic and routine surveillance studies resort to simplified indicators to measure dietary quality. Based on a previous study conducted by Caswell et al. on tablet-based data collection of 24-hour dietary recall (24hr-DR), we have developed and adapted a mobile tool collecting 24hr-DR among adults and children in Tanzania. Methods: Using the Tanzanian food composition table (FCT), the 24hr-DR was developed on an Android platform in Open Data Kit. The module provides food groups, food lists, meal list, ingredient list, quantity and amount consumed, breastfeeding frequency, and a recipe feature to collect detailed information (such as cooked and uncooked weights). Similar to the USDA Automated Multiple Pass Method, to accurately capture the dietary intake the tool contains summary features such as time in between meals and review of meals and portion size consumed in the previous day. Results: The mobile tool is currently used to collect dietary intake (1) among 960 children 0–18 months of age enrolled in the EFFECTS trial (ClinicalTrials.gov Identifier: NCT03759821) in Mara, Tanzania, and (2) among adult families enrolled in the DECIDE study in Dar es Salaam. Field workers were first trained on paper-based methods with food models followed by training on tablet-based collection. Because the tool was tailored with the Tanzanian FCT, conversion to nutrient intake for the individual are readily linked. This enables the investigators to look at dietary intake data in real time for quality assurance and analysis. Demonstration of the tool along with dietary profiles and analysis will be compared with the literature. The tool will be made available to the public in December 2019, and can be adapted to different contexts. Conclusions: Using mobile-based flexible platforms linked to a pre-existing FCT demystifies the "black box" processes of converting dietary intake to nutrient intake, thus reducing the time and labor needed using the traditional paper-based 24hr-DR method. Funding Sources: This study is funded through the Drivers of Food Choice Grants Program by Bill and Melinda Gates foundation and UK AID.